High-strength environmentally friendly steel paper and preparation method thereof

By adding dopamine-treated fibers in the preparation process of steel paper, combined with zinc chloride solution and current desalination technology, the problem of insufficient tensile strength and flexibility of steel paper in the existing technology is solved, and the preparation of high-strength environmentally friendly steel paper is realized. , improves fiber binding and mechanical properties.

CN118958030BActive Publication Date: 2024-12-24QIDONG JIEHUI NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411444239.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2024-12-24
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

The prior art has shortcomings in improving the tensile strength and flexibility of steel paper, especially in the selection of fiber components and optimization of gelation conditions, which leads to limited improvement in the strength of steel paper.

Method used

By adding dopamine to the slurry for stirring reaction, the hydrophilic unity between the fibers and surface roughening are promoted, and combined with the zinc chloride solution soaking, heating and pressurization and current desalting treatment, high-strength environmentally friendly steel paper is formed.

Benefits of technology

The tensile strength and flexibility of steel paper are significantly improved, and the bonding force between fibers is enhanced. The obtained steel paper has better mechanical properties and environmentally friendly characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention discloses high-strength environmentally friendly steel paper and a preparation method thereof. The present invention uses fibers from different sources as raw materials, treats the fibers with dopamine, and makes the hydrophilicity of different fibers the same or similar, thereby promoting the bonding between different fibers. At the same time, the dopamine treatment also roughens the fiber surface, enhances the friction between the fibers, thereby making the bonding between the fibers stronger, and the strength of the steel paper obtained is better.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of special paper, and in particular to a method for preparing high-strength environmentally friendly steel paper. Background Art

[0002] Steel paper is a special type of paper. Currently, it mainly uses environmentally friendly natural cellulose and its derivatives as raw materials. The base paper is obtained by gelling and compounding the cellulose, and then the steel paper base paper is stacked to obtain modified processed paper.

[0003] In the traditional method, natural fibers are treated with a gelling agent such as zinc chloride during fiber compounding to make the fibers fully swell and gel, promote the connection between the fibers, and thus greatly improve the strength of the obtained steel paper. With the advancement of science and technology, the requirements for the strength of steel paper have been strengthened. In order to further improve the strength of steel paper, various attempts have been made in this field. For example, Chinese patent document CN 104594127 A discloses a method for producing steel paper using sulfuric acid as a gelling agent. The method uses sulfuric acid as a gelling agent to gel and compound steel paper base paper, and then obtains the finished steel paper through deacidification, water washing, scrubbing, drying and other steps. The obtained steel paper has high tensile strength, good flexibility and good flatness, and solves the problems of low tensile strength, poor flexibility and variability of steel paper prepared using zinc chloride solution. However, the current research focus on improving tensile strength is on selecting or optimizing fiber components or how to increase gelling water, and there is little research on how to use existing fibers and gelling conditions to further improve the strength of composite fibers or steel paper.

[0004] The information in the background technology is only for illustrating the general background of the present invention and should not be regarded as admitting or suggesting in any form that such information constitutes the prior art known to a person skilled in the art. Summary of the invention

[0005] In order to solve at least some of the technical problems in the prior art, the present invention provides high-strength environmentally friendly steel paper and its slurry composition and preparation method. Specifically, the present invention includes the following contents.

[0006] In a first aspect, the present invention provides a method for preparing high-strength environmentally friendly steel paper, which comprises the steps of adding dopamine to pulp, stirring the reaction at a temperature of 40-80°C for 3-20 hours, and then allowing the pulp to enter a pulping machine for pulping, wherein the pulp contains 90-95 parts by weight of long fibers and 5-10 parts by weight of short fibers, the long fibers are cotton fibers with a length of 5-30 mm, and the short fibers are wood pulp fibers with a length of 1-2 mm, and the amount of dopamine added is 2-5% based on the total weight of the fibers in the pulp.

[0007] In certain embodiments, according to the method for preparing high-strength environmentally friendly steel paper of the present invention, after adding dopamine, oxygen is introduced into the slurry and the reaction is stirred.

[0008] In certain embodiments, according to the method for preparing high-strength environmentally friendly steel paper of the present invention, the dopamine is added to the slurry in the form of a solution of 0.5-5 mg / ml.

[0009] In certain embodiments, according to the method for preparing high-strength environmentally friendly steel paper of the present invention, the length of the long fibers is 3-10 times the length of the short fibers.

[0010] In certain embodiments, the method for preparing high-strength environmentally friendly steel paper according to the present invention further comprises a step of adjusting the pH to neutral before pulping.

[0011] In certain embodiments, the method for preparing high-strength environmentally friendly steel paper according to the present invention further comprises dilution and / or purification after pulping, and dehydration through a papermaking machine to form a wet paper web, and the water content is controlled in the range of 4-8% through pressing and drying to obtain steel paper base paper.

[0012] In certain embodiments, the method for preparing high-strength environmentally friendly steel paper according to the present invention further comprises soaking the multi-layer steel paper base paper in a 50-88 wt % zinc chloride solution for 1-10 minutes, and subjecting the soaked multi-layer steel paper base paper to heating, pressurizing, aging and desalting treatments.

[0013] In certain embodiments, according to the method for preparing high-strength environmentally friendly steel paper of the present invention, the desalination treatment comprises immersing the steel paper in water and applying direct current through the anode and cathode on both sides of the desalination tank.

[0014] In certain embodiments, the method for preparing high-strength environmentally friendly steel paper according to the present invention further comprises collecting the gas generated by the anode and introducing the gas into the slurry to which dopamine is added.

[0015] The second aspect of the present invention provides a high-strength environmentally friendly steel paper, which is prepared by the method described in the first aspect.

[0016] The present invention uses fibers from different sources as raw materials, and treats the fibers with dopamine to make the hydrophilicity of different fibers the same or similar, thereby promoting the bonding between different fibers. At the same time, the dopamine treatment also roughens the fiber surface, enhancing the friction between the fibers, thereby making the bonding between the fibers more firm, and the obtained steel paper has better strength. DETAILED DESCRIPTION

[0017] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0018] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that the upper and lower limits of the scope and each intermediate value therebetween are specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0019] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as commonly understood by those skilled in the art to which the invention belongs. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0020] In this article, the term "steel paper", sometimes also called "hardened paper" or "paper steel", refers to a high-hardness special paper made of fiber material. It has excellent elasticity, toughness, wear resistance and corrosion resistance, as well as good electrical insulation and mechanical strength. It can be used as mechanical parts such as gaskets.

[0021] Herein, the term "pulp" or "paper stock" refers to a fibrous material obtained by processing. Usually, the pulp further includes water to form a mixture. According to the fiber components of the pulp, the pulp is divided into plant fiber pulp, such as wood pulp (or wood fiber pulp), grass pulp (herbaceous plant such as stem fiber pulp), or inorganic material fiber pulp, such as glass fiber pulp. Usually, the pulp of the present invention is a mixture containing a variety of different fibers.

[0022] Herein, the term "length", when used as a fiber characteristic, generally refers to the fiber length of the initial raw material, especially the average length. During the pulp processing, different processing conditions may cause different degrees of degradation, shortening, etc. of the length of the initial raw material fiber.

[0023] [Preparation method]

[0024] In a first aspect of the present invention, a method for preparing high-strength environmentally friendly steel paper is provided, which comprises the step of treating different fibers with dopamine before pulping. Specifically, the method comprises the step of adding dopamine to the pulp, stirring and reacting at a temperature of 40-80° C. for 3-20 hours, and then allowing the pulp to enter a pulping machine for pulping.

[0025] Slurry:

[0026] In the present invention, the pulp contains different fibers, especially fibers of different compositions. For example, cotton fibers and wood pulp fibers have different hydrophilicity. That is, compared with cotton fibers, wood pulp fibers have stronger hydrophilicity. The inventors found that when the hydrophilicity is different, the bonding between the fibers is affected. For this reason, the present invention simultaneously treats the fibers with dopamine to form hydrophilic groups on the surfaces of the two fibers, so that the two fibers have similar or identical hydrophilicity.

[0027] In certain embodiments, in the pulp of the present invention, the amount of cotton fiber is 90-95 parts by weight, such as 91 parts by weight, 92 parts by weight, 93 parts by weight, 94 parts by weight, and 95 parts by weight. When the amount of cotton fiber is within the above range, the contact between the cotton fibers can be ensured, and the regulating effect of the wood pulp short fibers can be fully exerted.

[0028] The wood pulp fiber of the present invention is a short fiber made from woody plants as raw materials. The wood pulp fiber can be virgin wood pulp, recycled wood pulp or a mixture of the two in any proportion. The type of woody plant used as the raw material is not limited, and any woody plant known in the art can be selected, and its examples include but are not limited to broad-leaved plants such as birch, poplar, basswood, eucalyptus, maple, coniferous plants such as fish scale spruce, sand pine spruce, stinking fir, Korean pine, larch, Masson pine, etc.

[0029] In certain embodiments, the amount of the wood pulp fiber of the present invention is 5-10 parts by weight, such as 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight and 10 parts by weight. When the amount of the wood pulp fiber is within the above range, the wood pulp fiber can give full play to the hardness of the wood pulp fiber without affecting the bonding between the cotton fibers. If the amount of the wood pulp fiber is too high, the wood pulp fiber tends to be dispersed in large quantities between the long-fiber cotton fibers, which is not conducive to improving the contact and bonding between the cotton fibers, affecting the toughness of the steel paper. On the other hand, if the amount is too low, the cotton fibers tend to be excessively contacted, which is not conducive to improving the hardness of the steel paper.

[0030] Dopamine processing:

[0031] The dopamine treatment in the present invention comprises adding dopamine to the slurry, and stirring the reaction at a temperature of 40-80° C. for 3-20 hours.

[0032] In the present invention, the amount of dopamine added is generally 2-5%, such as 3%, 4% or 5%, based on the total weight of the fiber in the slurry. Within the above range, the fiber roughening treatment can be guaranteed without affecting the subsequent gelling reaction. If the amount is too high, the fiber tends to have low strength and is not conducive to the subsequent gelling, thereby affecting the strength of the steel paper. On the other hand, if the amount is too low, the fiber surface modification is insufficient and the degree of roughening is insufficient.

[0033] In the present invention, heating is preferably performed during the dopamine treatment, and the heating temperature is generally 40-80°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, etc. If the temperature is too high, although it is beneficial to the roughening treatment speed, the fiber tends to become darker in color. If the temperature is too low, the reaction is incomplete and the roughening is incomplete.

[0034] In the present invention, the dopamine treatment is preferably carried out under stirring conditions. The stirring can be carried out in any manner known in the art, and is not limited thereto.

[0035] In the present invention, the dopamine treatment time is not limited, and is generally within the range of 3-20 hours. Those skilled in the art can adjust it appropriately according to the concentration of dopamine and / or temperature. If the time is too long, the roughening treatment tends to be excessive, affecting the strength of a single fiber, and further affecting the strength of the obtained steel paper.

[0036] In the present invention, in order to accelerate the dopamine treatment, it is preferred to introduce an appropriate amount of oxygen into the slurry. The presence of oxygen accelerates the generation of polydopamine rough surface on the fiber surface by dopamine. The oxygen can be pure oxygen gas or can be introduced in the form of air.

[0037] Base paper preparation:

[0038] The base paper preparation of the present invention comprises the steps of allowing the pulp composition to enter a pulping machine for pulping treatment, then enter a pulping box for mixing, further undergoing dilution and / or purification treatment, and undergoing dehydration treatment through a papermaking machine to form a wet paper web, and controlling the water content in the range of 4-8% through pressing and drying to obtain steel paper base paper.

[0039] In the present invention, beating is performed in a pulping machine to increase the flexibility and interweaving of the fibers. The beating can be performed using a disc refiner, a conical refiner, or the like. The beating degree is controlled to be 15-25°SR, such as 16, 18, 20, 22, 24°SR; the wet weight is 8-18g, such as 9, 10, 12, 14, 16g, or the like. When preparing the slurry, the slurry is diluted to a solid content of 40-60% by weight. The purification treatment is used to remove fine impurities and particles. The purification method is not limited, and can be performed by, for example, precipitation, filtration, or flotation. Precipitation is the process of causing impurities to settle to the bottom by gravity. Filtration is the process of using filter media such as filter cloth or filter screen to intercept impurities. Flotation is the process of using bubbles to bring impurities to the surface of the slurry and remove them. The present invention can use any of the above methods or a combination of multiple methods for purification.

[0040] In the present invention, dehydration is a process of removing moisture from a mesh by vacuum to form wet paper. Pressing in the present invention further removes moisture. After pressing, the paper is transferred from the wet mesh to a wet machine, where heat transfer is used to achieve the purpose of drying, and then hot air drying is used to form base paper. In the present invention, the wet mesh can reduce the damage to the wet paper during the transfer process and maintain the flatness of the paper. The wet paper undergoes a wetting process on the wet mesh, which makes the cellulose fibers more tightly bonded, which is beneficial to the heat transfer effect in the subsequent drying process.

[0041] Next, the purpose of drying is achieved through heat transfer in a wet machine. The wet machine is the main equipment used for paper drying. The wet paper is heated by hot rollers and hot air to evaporate the moisture in the paper. In the wet machine, the wet paper is sent into the pressing area between the hot rollers. Under high pressure and high temperature, the moisture is squeezed out of the paper, making the surface of the paper dry. At the same time, the hot air heats the paper to increase the heat transfer effect and speed up the paper drying.

[0042] Gel treatment:

[0043] The gelling step of the present invention comprises soaking the multi-layer steel paper in a chemical solution for 1-10 minutes, such as 1 minute, 2 minutes, 2.5 minutes, 3 minutes, 3.5 minutes, etc.

[0044] In the present invention, gelation is performed in a gelation tank, and the temperature during gelation is not limited, for example, immersion gelation can be performed within the range of 15-40°C. Exemplary gelation temperatures include room temperature, 30°C, 35°C, 36°C, etc. The concentration of the medicine used in the present invention is generally 50-88% by weight of zinc chloride solution, preferably, the concentration of zinc chloride is 55% by weight, 60% by weight, 62% by weight, 64% by weight, 65% by weight, 68% by weight, 70% by weight, 75% by weight, 80% by weight, 85% by weight, etc.

[0045] Semi-finished product preparation:

[0046] The semi-finished product preparation step of the present invention includes heating and pressurizing the soaked multi-layer steel paper base paper to form a strong bond between the layers. Heating and pressurizing can be performed separately or simultaneously. Heating and pressurizing at the same time is more conducive to the bonding between the base paper layers, so it is preferred. The heating temperature of the present invention is generally 30-90°C, for example, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, etc. When heating at high temperature, it is preferably heated under wet heat conditions. The pressurization of the present invention is generally performed by a pressure roller, and the pressure size is not limited.

[0047] aging:

[0048] The step (4) of the present invention is aging, which includes aging treatment at 20-40°C. In the present invention, the aging treatment is carried out in an aging furnace, and the aging temperature is generally controlled at 25-40°C, such as 30°C, 32°C, 25°C, etc. The aging time is generally 30-120 minutes, such as 40 minutes, 50 minutes, 60 minutes, 70 minutes, 80 minutes, 90 minutes, etc. The aging time is generally related to the aging temperature. Generally, when the aging temperature is low, the aging treatment time is appropriately extended.

[0049] Desalting:

[0050] In the present invention, the desalination treatment step is not limited, and the exemplary desalination step is a stepwise desalination method, which includes allowing the steel paper to enter a plurality of cleaning tanks with gradually decreasing concentrations and finally pure water for desalination treatment. The concentration of zinc chloride in the cleaning tank is not limited, and exemplary, the concentration of zinc chloride in the cleaning tank is 60%, 30%, 15%, 8%, 4%, 2%, 1%, 0.5%, 0.05%, and 0. The desalination treatment time of each cleaning tank is controlled at 20-60 minutes, thereby making the surface of the steel paper smoother and more delicate.

[0051] Another exemplary desalination step is the electric current desalination method, which uses the electric field to cause the internal ions of the base paper to migrate in the water, and quickly move from the inside of the base paper to the water, thereby greatly improving the desalination effect and reducing the work intensity.

[0052] In the current desalination method of the present invention, the magnitude of the electric field is not limited, as long as the direction of the electric field remains substantially unchanged. The electric field of the present invention can be a variable electric field or a constant electric field.

[0053] In the current desalination method of the present invention, the electric field is generally generated by direct current, and the size of the direct current is generally 0.01-2A, such as 0.02A, 0.03A, 0.04A, 0.05A, 0.06A, 0.07A, 0.08A, 0.09A, 0.1A, 0.2A, 0.3A, 0.4A, 0.5A, 0.6A, 0.7A, 0.8A, 0.9A, 1.0A, 1.2A, 1.4A, 1.6A, 1.8A, etc. The size of the direct current of the present invention can be kept constant or arbitrarily changed within the above range. If the direct current is within the above range, the ions in the steel paper, especially the zinc ions, can be advantageously made to enter the water. The person skilled in the art can select the zinc chloride concentration in the steel paper, such as the estimated concentration, within the above range as required. If the direct current is too large, the zinc chloride entering the water tends to be electrolyzed, thereby affecting the electrode life cycle and causing energy waste. On the other hand, if the DC current is too small, the ions in the steel paper may not migrate sufficiently.

[0054] In the current desalination method of the present invention, the treatment time of the steel paper in the electric field is not limited, generally 1 second to 5 minutes. The salt component can be advantageously migrated into the water within the above time range. Those skilled in the art can select a suitable time according to the estimated concentration of zinc chloride in the steel paper, such as 5 seconds, 10 seconds, 15 seconds, 20 seconds, 25 seconds, 30 seconds, 35 seconds, 40 seconds, 45 seconds, 50 seconds, 55 seconds, 60 seconds, 65 seconds, 70 seconds, 80 seconds, 90 seconds, 100 seconds, 110 seconds, 120 seconds, 2.5 minutes, 3 minutes, 4 minutes, 5 minutes, etc. If the treatment time is too long, the zinc chloride entering the water tends to electrolyze, thereby affecting the electrode life cycle and causing energy waste. On the other hand, if the treatment time is too short, the migration of zinc chloride may be insufficient.

[0055] In the current desalination method of the present invention, in order to facilitate the migration of ions out of the steel paper, the angle between the direction of the electric field and the surface of the steel paper is preferably 45 0 More than 50 0 Above, 60 0 Above, 70 0 Above, 80 0 The above is most preferably substantially vertical.

[0056] In the electric current desalination method of the present invention, examples of water include, but are not limited to, pure water, clean water, tap water or purified natural water, such as river water, lake water or well water. Purified natural water generally refers to water after filtering to remove impurities.

[0057] In certain embodiments, the present invention has desalination carried out in a desalination tank. The desalination tank of the present invention is preferably a flat elongated structure, and its height is generally 5-50cm, for example 6cm, 8cm, 10cm, 12cm, 14cm, 16cm, 18cm, 20cm, 22cm, 24cm, 26cm, 28cm, 30cm, 34cm, 36cm, 38cm, 40cm, 42cm, 44cm, 46cm, etc. If the height is too high, the spacing between the positive and negative electrodes tends to become larger, causing excessive power consumption, which is not conducive to reducing costs. On the other hand, if the height is too low, the spacing between the positive and negative electrodes tends to become smaller, then it is easy to produce electrical breakdown, causing steel paper damage.

[0058] In the present invention, the length and width of the desalination tank are not limited, and are at least equivalent to the size of the steel paper or a multiple thereof. The desalination tank of the present invention preferably has the anode disposed at the top and the cathode disposed at the bottom. This design is conducive to the zinc ions migrating from the steel paper to the bottom of the desalination tank, thereby avoiding further contact between the steel paper and the zinc ions when the steel paper is taken out of the water, thereby avoiding possible further contamination of the steel paper.

[0059] In the present invention, the cathode of the desalination tank is used to move cations such as zinc ions to it, and is preferably an inert electrode material, examples of which include but are not limited to platinum, gold, silver, copper, chromium, carbon, etc. Exemplary cathodes include metal electrodes such as platinum electrodes, gold electrodes, silver electrodes, carbon (graphite, graphene, glassy carbon, etc.) electrodes, copper electrodes, chromium electrodes, oxide electrodes such as NiFe2O4-based electrodes, SnO2-based electrodes, CeO2-coated electrodes, etc.

[0060] In the present invention, the anode of the desalination tank is used to allow anions such as chloride ions to move thereto, and its material is not limited, and any material can be used, including the above-mentioned inert electrode.

[0061] In certain embodiments, during the desalination process of the present invention, it is preferred to fill the desalination tank with water so that the steel paper is immersed in the fluid, and preferably the steel paper is located approximately in the middle of the fluid in the desalination tank.

[0062] In certain embodiments, the present invention further comprises a step of collecting the gas generated during the electric field treatment, in particular, collecting the gas generated by the anode. The gas generated by the anode is mainly oxygen, which can be directly introduced into the slurry to promote dopamine treatment. In the continuous production process, the above scheme not only has the advantage of high efficiency of current desalination treatment, but also can make full use of the by-products of current desalination, achieve environmental protection and energy saving, and has excellent effect.

[0063] [High-strength steel paper]

[0064] The second aspect of the present invention provides a high-strength environmentally friendly steel paper. The steel paper of the present invention uses environmentally friendly plant-derived raw materials and is environmentally friendly. At the same time, under the same conditions, the steel paper of the present invention has higher strength and higher insulation strength than traditional steel paper.

[0065] The thickness of the steel paper of the present invention is not limited and can be any desired thickness. For example, the thickness of the environmentally friendly high-insulation steel paper of the present invention is 0.02-5 mm, such as 0.5 mm, 0.6 mm, 0.8 mm, 1 mm, 1.2 mm, 1.4 mm, 1.6 mm, 1.8 mm, 2.0 mm, 2.5 mm, 3.0 mm, 3.5 mm, 4.0 mm, 4.5 mm, etc. It should be noted that the above thickness range is only an exemplary thickness, and those skilled in the art can produce steel paper beyond the above thickness range as needed.

[0066] The density of the steel paper of the present invention is not specific. Under the same conditions, the steel paper of the present invention has a higher density than the conventional steel paper. The exemplary density of the steel paper of the present invention is generally 1-2.5 kg / dm 3 , for example 1.2-2.4kg / dm 3 , 1.4-2.2kg / dm 3 1.5-2.0kg / dm 31.6-1.8kg / dm 3 wait.

[0067] The form of the steel paper of the present invention is not limited and can be processed into any desired form. Exemplary forms include plates, sheets, films, foils or flat strips.

[0068] Example 1

[0069] 1. Pulping treatment

[0070] Add 5 mg / ml dopamine hydrochloride solution to the slurry until dopamine accounts for 5% of the total weight of the fiber in the slurry, adjust the pH value of the slurry to neutral, and stir the reaction at 40°C for 8 hours. Then, the slurry enters a pulping machine for beating, with a beating degree of about 19°SR and a wet weight of about 12g. Among them, the solid content of the slurry is about 65%, and the cotton fiber accounts for 90% by weight and the wood pulp fiber accounts for 10% by weight of the fiber in the slurry. The length of the cotton fiber is about 10 mm, and the length of the wood pulp fiber is 1-2 mm.

[0071] 2. Paper

[0072] The treated slurry then enters the slurry mixing box for mixing to ensure the slurry is uniform. It is further transported to the slurry mixing box for dilution to adjust the slurry concentration and purified to further remove impurities.

[0073] The diluted and purified pulp is dehydrated through the paper machine mesh, and then further dehydrated in the pressing section. It is then sent to the drying section for drying to control the water content in the range of 4-8% to obtain steel paper base paper.

[0074] 3. Gelation

[0075] The obtained 10 layers of steel paper are simultaneously conveyed by a conveying roller into a 60% zinc chloride solution for immersion for 1 minute to fully swell and gelatinize the fibers and promote the connection between the fibers. Next, the soaked 10 layers of paper are heated at 30-40°C for 20-30 minutes to further penetrate the zinc chloride and gelatinize the fibers. Then, the layers of paper are hot-pressed to tightly bond together to form a semi-finished product.

[0076] 4. Post-processing

[0077] The semi-finished product is sent to an aging furnace and aged at 20-40°C for about 50 minutes to improve the stability of the internal structure of the steel paper.

[0078] After aging, the steel paper is sequentially placed in multiple cleaning tanks with gradually decreasing concentrations and finally pure water for desalination treatment. The zinc chloride concentrations in the cleaning tanks are 60%, 30%, 15%, 8%, 4%, 2%, 1%, 0.5%, 0.05%, and 0. The desalination treatment time of each cleaning tank is controlled at 20-60 minutes, thereby making the surface of the steel paper smoother and more delicate. The product is dried.

[0079] Example 2

[0080] 1. Pulping treatment

[0081] Add 5 mg / ml dopamine hydrochloride solution to the slurry until dopamine accounts for 3% of the total weight of the fiber in the slurry, adjust the pH value of the slurry to neutral, and stir the reaction at 50°C for 4 hours. Then, the slurry enters a pulping machine for beating, with a beating degree of about 19°SR and a wet weight of about 12g. Among them, the solid content of the slurry is about 65%, and the cotton fiber accounts for 90% by weight and the wood pulp fiber accounts for 10% by weight of the fiber in the slurry. The length of the cotton fiber is about 10 mm, and the length of the wood pulp fiber is 1-2 mm.

[0082] 2. Paper

[0083] The treated slurry then enters the slurry mixing box for mixing to ensure the slurry is uniform. It is further transported to the slurry mixing box for dilution to adjust the slurry concentration and purified to further remove impurities.

[0084] The diluted and purified pulp is dehydrated through the paper machine mesh, and then further dehydrated in the pressing section. It is then sent to the drying section for drying to control the water content below 5% to obtain steel paper base paper.

[0085] 3. Gelation

[0086] The obtained 10 layers of steel paper are simultaneously conveyed by a conveying roller into a 60% zinc chloride solution for immersion for 1 minute to fully swell and gelatinize the fibers and promote the connection between the fibers. Next, the soaked 10 layers of paper are heated at 30-40°C for 20-30 minutes to further penetrate the zinc chloride and gelatinize the fibers. Then, the layers of paper are hot-pressed to tightly bond together to form a semi-finished product.

[0087] 4. Post-processing

[0088] The semi-finished product is sent to an aging furnace and aged at 20-40°C for about 50 minutes to improve the stability of the internal structure of the steel paper.

[0089] After aging, the steel paper is sequentially placed in multiple cleaning tanks with gradually decreasing concentrations and finally pure water for desalination treatment. The zinc chloride concentrations in the cleaning tanks are 60%, 30%, 15%, 8%, 4%, 2%, 1%, 0.5%, 0.05%, and 0. The desalination treatment time of each cleaning tank is controlled at 20-60 minutes, thereby making the surface of the steel paper smoother and more delicate. The product is dried.

[0090] Example 3

[0091] 1. Pulping treatment

[0092] Add 5 mg / ml dopamine hydrochloride solution to the slurry until dopamine accounts for 5% of the total weight of the fiber in the slurry, adjust the pH value of the slurry to neutral, and stir and react for 2 hours under oxygen conditions at a temperature of 40°C. Then, the slurry enters a pulping machine for beating, with a beating degree of about 19°SR and a wet weight of about 12g. Among them, the solid content of the slurry is about 65%, and the cotton fiber accounts for 90% by weight and the wood pulp fiber accounts for 10% by weight of the fiber in the slurry. The length of the cotton fiber is about 10 mm, and the length of the wood pulp fiber is 1-2 mm.

[0093] 2. Paper

[0094] The treated slurry then enters the slurry mixing box for mixing to ensure the slurry is uniform. It is further transported to the slurry mixing box for dilution to adjust the slurry concentration and purified to further remove impurities.

[0095] The diluted and purified pulp is dehydrated through the paper machine mesh, and then further dehydrated in the pressing section. It is then sent to the drying section for drying to control the water content in the range of 4-8% to obtain steel paper base paper.

[0096] 3. Gelation

[0097] The obtained 10 layers of steel paper are simultaneously conveyed by a conveying roller into a 60% zinc chloride solution for immersion for 1 minute to fully swell and gelatinize the fibers and promote the connection between the fibers. Next, the soaked 10 layers of paper are heated at 30-40°C for 20-30 minutes to further penetrate the zinc chloride and gelatinize the fibers. Then, the layers of paper are hot-pressed to tightly bond together to form a semi-finished product.

[0098] 4. Post-processing

[0099] The semi-finished product is sent to an aging furnace and aged at 20-40°C for about 50 minutes to improve the stability of the internal structure of the steel paper.

[0100] After aging, the steel paper is sequentially placed in multiple cleaning tanks with gradually decreasing concentrations and finally pure water for desalination treatment. The zinc chloride concentrations in the cleaning tanks are 60%, 30%, 15%, 8%, 4%, 2%, 1%, 0.5%, 0.05%, and 0. The desalination treatment time of each cleaning tank is controlled at 20-60 minutes, thereby making the surface of the steel paper smoother and more delicate. The product is dried.

[0101] Example 4

[0102] 1. Pulping treatment

[0103] Add 5 mg / ml dopamine hydrochloride solution to the slurry until dopamine accounts for 5% of the total weight of the fiber in the slurry, and adjust the slurry pH to neutral. Stir and react for 2 hours under oxygen conditions at 40°C. Then let the slurry enter a pulping machine for beating, with a beating degree of about 19°SR and a wet weight of about 12g. Among them, the solid content of the slurry is about 65%, and the cotton fiber accounts for 90% by weight and the wood pulp fiber accounts for 10% by weight of the fiber in the slurry. The length of the cotton fiber is about 10 mm, and the length of the wood pulp fiber is 1-2 mm.

[0104] 2. Paper

[0105] The treated slurry then enters the slurry mixing box for mixing to ensure the slurry is uniform. It is further transported to the slurry mixing box for dilution to adjust the slurry concentration and purified to further remove impurities.

[0106] The diluted and purified pulp is dehydrated through the paper machine mesh, and then further dehydrated in the pressing section. It is then sent to the drying section for drying to control the water content below 5% to obtain steel paper base paper.

[0107] 3. Gelation

[0108] The obtained 10 layers of steel paper are simultaneously conveyed by a conveying roller into a 60% zinc chloride solution for immersion for 1 minute to fully swell and gelatinize the fibers and promote the connection between the fibers. Next, the soaked 10 layers of paper are heated at 30-40°C for 20-30 minutes to further penetrate the zinc chloride and gelatinize the fibers. Then, the layers of paper are hot-pressed to tightly bond together to form a semi-finished product.

[0109] 4. Post-processing

[0110] The semi-finished product is sent to an aging furnace and aged at 20-40°C for about 50 minutes to improve the stability of the internal structure of the steel paper.

[0111] After aging, the steel paper is placed horizontally into a desalination tank filled with clean water under ventilation conditions. The height of the desalination tank is about 10 cm. A graphene electrode is set as an anode on the top of the desalination tank and a graphene electrode is set as a cathode on the bottom. The position of the steel paper in the clean water is adjusted so that it is completely immersed in the water. A 0.02A direct current is applied to the top and bottom of the desalination tank for 30 seconds. Then it is transferred to the clean water tank for washing, taken out and dried to a moisture content of less than 5%. At the same time, the gas generated by the anode is collected and passed through the gas storage pipe to the oxygen gas during dopamine treatment.

[0112] Comparative Example 1

[0113] 1. Pulping treatment

[0114] The pulp is put into a pulping machine for beating, with a beating degree of about 19°SR and a wet weight of about 12g. The solid content of the pulp is about 65%, and the cotton fiber accounts for 90% by weight and the wood pulp fiber accounts for 10% by weight of the pulp fiber. The length of the cotton fiber is about 10mm, and the length of the wood pulp fiber is 1-2mm.

[0115] 2. Paper

[0116] The treated slurry then enters the slurry mixing box for mixing to ensure the slurry is uniform. It is further transported to the slurry mixing box for dilution to adjust the slurry concentration and purified to further remove impurities.

[0117] The diluted and purified pulp is dehydrated through the paper machine mesh, and then further dehydrated in the pressing section. It is then sent to the drying section for drying to control the water content in the range of 4-8% to obtain steel paper base paper.

[0118] 3. Gelation

[0119] The obtained 10 layers of steel paper are simultaneously conveyed by a conveying roller into a 60% zinc chloride solution for immersion for 1 minute to fully swell and gelatinize the fibers and promote the connection between the fibers. Next, the soaked 10 layers of paper are heated at 30-40°C for 20-30 minutes to further penetrate the zinc chloride and gelatinize the fibers. Then, the layers of paper are hot-pressed to tightly bond together to form a semi-finished product.

[0120] 4. Post-processing

[0121] The semi-finished product is sent to an aging furnace and aged at 20-40°C for about 50 minutes to improve the stability of the internal structure of the steel paper.

[0122] After aging, the steel paper is sequentially placed in multiple cleaning tanks with gradually decreasing concentrations and finally pure water for desalination treatment. The zinc chloride concentrations in the cleaning tanks are 60%, 30%, 15%, 8%, 4%, 2%, 1%, 0.5%, 0.05%, and 0. The desalination treatment time of each cleaning tank is controlled at 20-60 minutes, thereby making the surface of the steel paper smoother and more delicate. The product is dried.

[0123] Comparative Example 2

[0124] 1. Pulping treatment

[0125] Add 5 mg / ml dopamine hydrochloride solution to the slurry until dopamine accounts for 5% of the total weight of the fiber in the slurry, adjust the pH value of the slurry to neutral, and stir the reaction at 50°C for 24 hours. Then, the slurry enters a pulping machine for beating, with a beating degree of about 19°SR and a wet weight of about 12g. Among them, the solid content of the slurry is about 65%, and the cotton fiber accounts for 90% by weight and the wood pulp fiber accounts for 10% by weight of the fiber in the slurry. The length of the cotton fiber is about 10 mm, and the length of the wood pulp fiber is 1-2 mm.

[0126] 2. Paper

[0127] The treated slurry then enters the slurry mixing box for mixing to ensure the slurry is uniform. It is further transported to the slurry mixing box for dilution to adjust the slurry concentration and purified to further remove impurities.

[0128] The diluted and purified pulp is dehydrated through the paper machine mesh, and then further dehydrated in the pressing section. It is then sent to the drying section for drying to control the water content in the range of 4-8% to obtain steel paper base paper.

[0129] 3. Gelation

[0130] The obtained 10 layers of steel paper are simultaneously conveyed by a conveying roller into a 60% zinc chloride solution for immersion for 1 minute to fully swell and gelatinize the fibers and promote the connection between the fibers. Next, the soaked 10 layers of paper are heated at 30-40°C for 20-30 minutes to further penetrate the zinc chloride and gelatinize the fibers. Then, the layers of paper are hot-pressed to tightly bond together to form a semi-finished product.

[0131] 4. Post-processing

[0132] The semi-finished product is sent to an aging furnace and aged at 20-40°C for about 50 minutes to improve the stability of the internal structure of the steel paper.

[0133] After aging, the steel paper is sequentially placed in multiple cleaning tanks with gradually decreasing concentrations and finally pure water for desalination treatment. The zinc chloride concentrations in the cleaning tanks are 60%, 30%, 15%, 8%, 4%, 2%, 1%, 0.5%, 0.05%, and 0. The desalination treatment time of each cleaning tank is controlled at 20-60 minutes, thereby making the surface of the steel paper smoother and more delicate. The product is dried.

[0134] Test Case

[0135] 1. Electrical strength test of insulation materials

[0136] According to GB / T 1408.1-2016 "Electrical strength test methods for insulating materials Part 1: Tests at power frequency", the dielectric strength of steel paper under power frequency (50Hz) voltage is measured. The specific steps are as follows:

[0137] Sample preparation:

[0138] The thickness of the sample is 3 mm, and the two surfaces of the sample in contact with the electrode should be parallel and as flat and smooth as possible.

[0139] Electrode preparation:

[0140] Stainless steel rods are usually used as electrodes with a diameter of 6 ± 0.1 mm and a rounded edge radius of 1 ± 0.2 mm. The electrodes should be installed vertically in the electrode holder so that one electrode is above the other. The gap between the protected electrode and the guarding electrode is twice the thickness of the sample. The diameter of the protected electrode is 10 times the thickness of the sample.

[0141] Test conditions:

[0142] The test is carried out under environmental conditions of 23±2℃ and 50±5%RH. The specimens are conditioned under these conditions for at least 24 hours. The thickness of the specimens is measured to 0.1mm.

[0143] Test process:

[0144] The sample is placed between two electrodes in a stretched state. The voltage applied to the sample starts from zero and gradually increases at a uniform rate (such as 500V / s) until breakdown occurs.

[0145] The electrical strength is the ratio of the breakdown voltage to the electrode spacing, and the median value of three samples is taken as the final result.

[0146] Data recording and analysis:

[0147] The breakdown voltage and electrical strength of each specimen were recorded.

[0148] 2. Tensile Strength Measurement Experiment

[0149] According to GB / T 12914-2018 "Paper and paperboard - Determination of tensile strength - Constant tension method (20mm / min)", use a tensile tester to stretch a sample of specified size to break at a constant tensile speed, record its tensile force and elongation at the same time. Continuously record the tensile force and elongation, and determine the elongation at break, tensile energy absorption and elastic modulus. The specific steps are as follows:

[0150] 1. Adjustment and calibration of the tester

[0151] The tester should be calibrated according to the manufacturer's instructions so that the elongation at break is accurate to ±0.1 mm. Correctly set the grip position to check the test length. Adjust the test speed. Adjust the clamping pressure so that the specimen does not slip or get damaged.

[0152] 2. Sample preparation

[0153] The tensile index is determined according to GB / T451.2. If the elastic modulus needs to be determined, the thickness of the sample is determined according to GB / T451.2. From the non-destructive sample, cut a sample with a width of 15mm±0.1mm and hold it between the two ends. Avoid touching the test area of ​​the sample with bare hands. There should be no watermarks, creases and wrinkles in the test area. Ensure that the sample is representative of the sample being tested. The two long sides of the sample should be straight, and its parallelism should not exceed ±0.1 mm throughout the clamping length. The incision should be neat and undamaged. Cut a sufficient number of samples to perform 10 tests in each required direction (longitudinal or transverse).

[0154] 3. Test steps

[0155] Make sure the tester has been calibrated as above. Place the specimen in the grips and gently straighten the specimen to eliminate any visible slack. Avoid touching the test area between the grips with your fingers. Grip the specimen firmly and test. Perform 10 tests in each required direction (longitudinal or transverse).

[0156] 4. Technical parameters

[0157] Measuring range: 50N, 100N, 200N, etc. optional

[0158] Resolution: 0.01N

[0159] Accuracy: ±1%

[0160] Test speed: (5-500) mm / min

[0161] Return speed: 300 mm / min adjustable

[0162] Test stroke: 680mm adjustable

[0163] Dimensions: 400×500×1200 mm

[0164] Mass: Approx. 68kg.

[0165] Table 1

[0166]

[0167] Although the present invention has been described with reference to exemplary embodiments, it should be understood that the present invention is not limited to the disclosed exemplary embodiments. Various adjustments or changes may be made to the exemplary embodiments of the present specification without departing from the scope or spirit of the present invention. The scope of the claims should be based on the broadest interpretation to cover all modifications and equivalent structures and functions.

Claims

1. A method for improving the breakdown voltage of environmentally friendly steel paper, characterized in that: The method comprises the steps of adding dopamine to the pulp, stirring and reacting at a temperature of 40-45° C. for 3-20 hours, and then allowing the pulp to enter a pulping machine for pulping, wherein oxygen is introduced into the pulp after adding dopamine and stirring and reacting, and before pulping, further comprising the step of adjusting the pH to neutral, wherein the pulp comprises 90-93 parts by weight of long fibers and 7-10 parts by weight of short fibers, wherein the long fibers are cotton fibers with a length of 5-30 mm, and the short fibers are wood pulp fibers with a length of 1-2 mm, and the amount of dopamine added is 2-5% based on the total weight of the fibers in the pulp; The method further comprises the following steps: further diluting and / or purifying the pulp, and performing a dehydration process on a paper machine to form a wet paper web, and then pressing and drying the wet paper web to obtain a steel paper base paper; The method further includes soaking the multi-layer steel paper base paper in zinc chloride solution, and heating, pressurizing, aging and desalting the soaked multi-layer steel paper base paper. The desalting treatment includes immersing the steel paper in water, and applying direct current through the anode and cathode on both sides of the desalting tank. The electric field causes the ions inside the base paper to migrate in the water, moving from the inside of the base paper to the water. The magnitude of the direct current is 0.01-2A, and the treatment time is 1 second to 5 minutes.

2. The method according to claim 1, characterized in that The dopamine was added to the slurry in the form of a 0.5-5 mg / ml solution.

3. The method according to claim 1, characterized in that The length of the long fibers is 3-10 times the length of the short fibers.

4. The method according to claim 1, characterized in that: The moisture content is controlled within the range of 4-8% by pressing and drying to obtain steel paper base paper.

5. The method according to claim 4, characterized in that The multi-layer steel paper base paper is immersed in a 50-88 wt% zinc chloride solution for 1-10 minutes.

6. The method according to claim 1, characterized in that The method further comprises collecting the gas generated by the anode and introducing the gas into the slurry after adding dopamine.

7. A high-strength environmentally friendly steel paper with improved breakdown voltage, characterized in that: It is obtained by treating with the method according to any one of claims 1 to 6.